SPECIFICITY OF THE DIRECT METHOD OF TEACHING A FOREIGN LANGUAGE - Begizova Madina Karimovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: The article focuses on the direct method - one of the fruitful methods widely applied in teaching a foreign language at present. Apart from its various positive sides, there are revealed some of its downsides which can be done away with in case the method in question is used in combination with other methods.